Understanding how hedonic motivation, perceived benefit, and attitude influence staycation intention: A study in Surabaya - Wibisono, Gabriel Michelle; Kusumawidjaya, Erris (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
Staycation has become a form of tourism alternative since the hit of COVID-19 pandemic because of the many restrictions that hampered long-distance vacation activities. In the current post-pandemic era, there must certainly be other driving factors that can encourage someone’s intention to choose staycation rather than to travel to a further place. Therefore, this research intends to test the influence of hedonic motivation, perceived benefits, and attitudes on the intention to go on a staycation in Surabaya, Indonesia. The study sample amounted to 210 respondents categorized as productive people living in Surabaya. This study leverages the SmartPLS software for the SEM-PLS analysis technique. Results of this study show that hedonic motivation and perceived benefit significantly and positively influence attitude. While hedonic motivation influences staycation intention, both directly and indirectly through attitude, perceived benefit has only indirect effect towards staycation intention with attitude that serves as a mediator. This study aims at providing an overview of the relationship between hedonic motivation, perceived benefits, and attitudes toward the intention to go on a staycation in Surabaya. By knowing the influence of each of these factors, the industry of tourism and hospitality can formulate more effective and targeted strategies in the current conditions.